Basal-bolus Therapy in Patients with Type 2 Diabetes Mellitus in the UK: Patient Characteristics, Treatment Patterns and the Effect of Switching to Premixed Insulin. Issue 4 (December 2016) - Brunt, Kate; Curtis, Bradley; Ivanyi, Tibor; Balogh, Elemer; Chalkiadaki, Corina; MacLachlan, Sharon; Neasham, David; Raluy-Callado, Mireia
Abstract Introduction Increasing emphasis is being placed on insulin use among patients with type 2 diabetes mellitus (T2DM). Basal-bolus (BB) therapy is regarded as the gold standard, but a high frequency of injections and the general complexity of this therapy are seen as barriers in real-world practice. Here we describe the characteristics and treatment patterns of patients with T2DM receiving BB in the UK, with specific focus on those switching to a simplified regimen of premixed insulin. Methods Patients with T2DM receiving BB from 1 January 2005 were identified from the Clinical Practice Research Datalink. Characteristics were described at treatment initiation or on 1 January 2005, and treatment patterns were assessed at 12 months of follow-up. Clinical factors were compared in two groups of patients who while receiving BB had one haemoglobin A1c (HbA1c) measurement of ≥53 mmol/mol (7.0%) and remained either on BB or switched to a premixed insulin regimen. Results Study criteria were met by 12, 060 subjects (mean age 59 years; duration diabetes 12.4 years). The mean HbA1c concentration was 76 mmol/mol (9.1% of patients), and 84.0% of patients were overweight. At 12 months of follow-up, 74.5% of the patients who had started BB remained on it. While on BB, 8835 patients had a HbA1c measurement of ≥53 mmol/mol (7.0% of all patients); of these, 95.9% remained on BB and 4.1% switched to premixed insulin. Mean HbA1c levels were consistently higher for patients who switched to premixed insulin than for those who remained on BB, but the levels remained relatively unchanged over time. Conclusion A large proportion of patients receiving insulin did not achieve good glycaemic control in clinical practice. A small subset with higher comorbidities and HbA1c levels switched to a simplified regimen. Little evidence was found that type of insulin therapy was associated with meaningful changes in key clinical factors over time. Funding Eli Lilly and company.